Tip pruning for synchronized vegetative growth and controlling alternate bearing in mango (Mangifera indica) - BARMAN, P; MISHRA, D (The Indian Journal of Agricultural Sciences, 2018)
Alternate bearing in many mango (Mangifera indica L.) cultivars including Dashehari is one of the main hurdles in maximising fruit production thus causing a major threat to the expansion of mango industry. Therefore an experiment was conducted for four consecutive years on 10-12 years mango cv. Dashehari spaced at 7.5 m x 7.5 m to induce synchronous vegetative growth to get same physiological stage of shoots for regular uniform flowering and fruiting in mango cv. Dashehari. For this purpose, whole tree was tip pruned just below first node after crop harvest and thereafter drenched with paclobutrazol @ 3.2 ml/m canopy diameter during September. Tip pruning was also performed in October to study its effect on panicle emergence bypassing vegetative flushing. The result exhibited significant influence of post-harvest pruning cum paclobutrazol application on uniform flowering, fruit yield and quality parameters while October pruning had positive effects on light availability below tree canopy, however increased vegetative growth at the expense of flowering and fruiting. Thus whole tree tip pruning after harvest of off year fruits followed by soil drenching with paclobutrazol, a month prior to flower bud differentiation, could be adopted for regulating flowering and fruiting during off year.